Characterization of Burkholderia sp. strain CJ1, a newly isolated berberine-degrading bacterium from rhizosphere of Coptis japonica. Issue 6 (2nd June 2020) - Yoshida, Hinaka; Takeda, Hisashi; Wakana, Daigo; Hosoe, Tomoo
ABSTRACT: Burkholderia sp. strain CJ1 was newly isolated as berberine (BBR) degrading bacteria from rhizosphere of Coptis japonica . CJ1 had the ability to utilize BBR as the sole carbon source and revealed that BBR metabolism via 11-hydroxylation and demethylenation pathway. It was also revealed that the 11-hydroxylation ability of BBR and palmatine (PAL) has induced by BBR.